Implementasi Model Pembelajaran Cooperative Tipe Team Assisted Individualization untuk Meningkatkan Hasil Belajar Matematika Siswa: Indonesia - Yundri Akhyar; Murtiningsih; Zalisman; Syahri Ramadhan; Evi Rahayu (Al-Mafahim: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This study aims to improve students' mathematics learning outcomes using the Team Assisted Individualization type cooperative learning model against the background of low Mathematics learning outcomes in the distribution material. This research was conducted in two cycles and each cycle was conducted in two meetings. For this classroom action research to run well, the researcher arranges the stages that are passed in classroom action research, namely planning, action research, action observation, and reflection. The subjects in this study were teachers and students of Class 3 B SD Negeri 44 Pekanbaru, amounting to 34 people. Data collection techniques were carried out by observation, documentation, and test techniques. The results showed that the application of Team Assisted Individualization type cooperative learning could improve student learning outcomes. These results can be seen from the first cycle of student success reaching 64.7% and in the second cycle increasing to 91.18% with the 'Very Good' category. This proves that the application of Team Assisted Individualization type cooperative learning can improve mathematics learning outcomes in the distribution of materials for Class 3B students at SD Negeri 44 Pekanbaru.